PRESCRIBING PHYSICAL ACTIVITY AS MEDICINE- THE NEED TO LOOK AHEAD & BEYOND - Azam, Naila (Pakistan Armed Forces Medical Journal, 2019)
Culture of physical fitness has been considered important in primitive civilizations; even being imbibed as religious rituals based on dancing. Earliest records from ancient China; 2500 BC reveal recognition of organized exercise, as a formal means of health promotion. Chinese surgeons also suggested exercises modelled on the movement of animals; especially the Tiger, as a means to stay healthy and agile. Kung Fu; the common violent combat connotation is also a form of medical gymnastics like yoga. Evaluation of scaled-up PA interventions is important in order to increase practice-based evidence on effective PA promotion and tackle the global pandemic of population inactivity. Changes in priority and investment in health promotion programs affect reach, adoption, and effectiveness by strongly embedding Physical Physical Activity As Medicine Activity promotion as a Bonafide prescription in the healthcare delivery system.